PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY (CRH) DI MTsN 1 PADANGSIIDMPUAN - nuhabibi s (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to describe the improvement of students’ mathematical problem solving ability by applying cooperative learning model of CRH type at the eighth grade students of MTsN 1 Padangsidimpuan. The research was conducted by using Class Action Research (CAR) with 36 students as the subject. Test, questionnaire, field note, and documentation were used in collecting the data. The research consists of two cycles. The first cycle showed (a) the average of students’ mathematical problem solving ability was 75.07 and (b) the average of using cooperative learning model of CRH type was 74.60 ( enough category).The second cycle showed (a) the average of students’ mathematical problem solving ability was 83.35 and (b) the average of using cooperative learning model of CRH type was 90.08 (very good category).It was concluded applyingcooperative learning model of CRH type got the improvement on students’ mathematical problem solving ability at the eighth grade students of MTsN 1 Padangsidimpuan.